Evaluasi Fungsi Penghijauan pada Median Jalan yang Direndahkan di Jalan Prof. Dr. Ida Bagus Mantra, Bali - Sanjaya, I Gusti Gede Arya; Asmiwyati, I Gusti Agung Ayu Rai; Sukewijaya, I Made (Jurnal Arsitektur Lansekap, 2023)
Evaluation of the Greening Function at the Lowered Road Median on the Jalan Prof. Dr. Ida Bagus Mantra, Bali. Prof. Dr. Ida Bagus Mantra highway is one of the bypass roads in Bali that was created to avoid congestion on the southern side of the island of Bali. This study aims to evaluate the function of the greening of the lowered median on that road and make recommendations as a solution. The method used was observation with the guidance of assessment criteria to obtain data on the function of a shade, glare barrier, and identity giver. To evaluate the function of aesthetic, the method used was observation and Scenic Beauty Estimation (SBE) questionnaire. The interview method was used to obtain data related to plant maintenance, and literature study method was used to obtain secondary data that support research. The results of this study indicate the shade function gets a good category with an average score of 75.6%, the glare barrier function gets a bad category with an average score of 25.9%, and the identity giver function gets a bad category with an average score of 35, 7%. Assesment of the aesthetic function showed 14 photos of low beauty, 30 of medium beauty, and 4 photos of high beauty were obtained. Recommendations given by researchers in the form of arrangement and maintenance recommendations, where the arrangement recommendations emphasize the addition of the number and type of plants.